Investigation of Chernobyl 4-th unit materials by gamma activation method - Dikiy, N.P.; Dovbnya, A.N.; Karnaukhov, I.M.; Lyashko, Yu.V.; Mazilov, A.V.; Shevyakova, E.P.; Tolstolutskiy, A.G.; Uvarov, V.L.; Glygalo, V.N.; Rudya, K.G. (Вопросы атомной науки и техники, 2002)
Isotope and element content the samples of Chornobyl 4-th wrecking unit materials (concrete fragments and lava-like materials) were investigated by γ-activation method using bremsstrahlung of the electron accelerator. The concentration of a number of nuclides (U-238, Cs-137, Sr-90, Ni-58, Zr-90 etc.) and their depth distribution into concrete were determined as well as the corresponding correlation ratio. The comparison of the obtained data with the structure-phase analysis results was carried out.